Twenty-eight years of experience measuring autonomy using the Dempster Practice Behavior Scale. Issue 10 (October 2020) - Goolsby, Mary Jo; Pierson, Charon A.; Sheer, Barbara
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: Autonomy in practice is an important attribute of all professions and a cornerstone of advanced nursing practice. The Dempster Practice Behavior Scale was conceptualized, constructed, and psychometrically tested to make available a generalizable, empirically sound, and useful tool capable of measuring previously unrecognized dimensions of autonomy in practice. Nurse practitioner (NP) practice continues to evolve as new models of care emerge, requiring more autonomy in the NP role. Purpose: The purpose was to describe the development and psychometric testing of the Dempster Practice Behavior Scale (DPBS), review the extant research on its use in research on nursing and other professions, and determine where future research is needed on the concept of autonomy in professional practice with a focus on advanced practice registered nurses (APRNs). Methods: Research articles, theses, dissertations using the DPBS as an instrument to measure practice autonomy were reviewed. Results: Twenty-one unique publications were examined for reports of psychometric properties in various populations. For the APRN population (total N = 1, 669 in 10 studies), psychometrics for the DPBS support the reliability of the instrument for research. The remaining 11 studies included 2, 285 participants who were not APRNs. Implications for practice: Questions remain about the relationships between autonomy and external factors such as regulatory environment, practice setting, models of care, years of experience, and practice mix.